2009
DOI: 10.1038/sj.bjc.6605248
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of human tumour prostate PC-3 cell growth by cannabinoids R(+)-Methanandamide and JWH-015: Involvement of CB2

Abstract: Background:We have previously shown that cannabinoids induce growth inhibition and apoptosis in prostate cancer PC-3 cells, which express high levels of cannabinoid receptor types 1 and 2 (CB1 and CB2). In this study, we investigated the role of CB2 receptor in the anti-proliferative action of cannabinoids and the signal transduction triggered by receptor ligation.Methods:The human prostate cancer cell lines, namely PC-3, DU-145 and LNCaP, were used for this study. Cell proliferation was measured using MTT pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
82
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(84 citation statements)
references
References 55 publications
(78 reference statements)
2
82
0
Order By: Relevance
“…So it is possible that Cnr2 activation inhibits the phosphorylation of JNK and subsequently inhibits the transcription of alox5 through reducing the level of cAMP. Our finding that the JNKc-Jun-Alox5 axis could be efficiently blocked by Cnr2 signaling activation is consistent with the previous observation that Cnr2 activation inhibits human tumor cell proliferation by downregulating the phosphorylation of JNK (58).…”
Section: Discussionsupporting
confidence: 80%
“…So it is possible that Cnr2 activation inhibits the phosphorylation of JNK and subsequently inhibits the transcription of alox5 through reducing the level of cAMP. Our finding that the JNKc-Jun-Alox5 axis could be efficiently blocked by Cnr2 signaling activation is consistent with the previous observation that Cnr2 activation inhibits human tumor cell proliferation by downregulating the phosphorylation of JNK (58).…”
Section: Discussionsupporting
confidence: 80%
“…Recently, numerous studies have evidenced the role of cannabinoids as potential anti-tumoral drugs owing to their ability to reduce tumor in different animal models, including glioma, 6 breast cancer 7,8 and prostate cancer. 9,10 Recent research has also reported that the synthetic cannabinoid WIN-55 212-2 inhibits HCC growth. 11,12 It has been described that D 9 -tetrahydrocannabinol (D 9 -THC), the main active constituent of marijuana, triggers human glioma cell death through stimulation of an ER stress pathway that activates autophagy and promotes apoptosis.…”
mentioning
confidence: 99%
“…The effects of anandamide in LNCaP, DU145, and PC3 cells were mediated through down-regulation of epidermal growth factor receptor (EGFR) and accumulation of ceramide [77]. JWH-015 triggered a de novo synthesis of ceramide, which induced cell death, followed by JNK (c-Jun N-terminal kinase) activation and Akt inhibition [76]. Effects of R(+)-Methanandamide and JWH-015 were rescued by treatment with SR 144528 in PC-3 cells [76, 79].…”
Section: Introductionmentioning
confidence: 99%